Control of fixed wing unmanned aerial vehicles in autonomous variable shape formation flight - Cordeiro, Thiago Felippe Kurudez (2018)
Tese (doutorado)—Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2018.